English Language Learners’ Strategy Use and Self-Efficacy Beliefs in English Language Learning - Shi, Hong (Journal of International Students, 2018)
This study examined self-efficacy and language strategy use of college-level English Language Learners (ELLs) at a southeastern university in the United States. It analyzed the relationship between self-efficacy and strategy use. An English Language Learning Survey was used to collect data from 198 college-level ELLs. Participants had positive self-efficacy toward their English learning and the most often used strategies were compensation, social and metacognitive strategies. Self-efficacy was positively correlated with cognitive, compensation, memory, metacognitive, and social strategy. The study suggested that teachers provide scaffolding for ELLs through strategy instruction. Teachers can teach self-regulated learning strategies and focus on ELLs’ improvement and mastery of content to enhance their self-efficacy, language proficiency and learning autonomy required for their academic courses learning.